Jézus missziójának célja - LÉSZAI, Lehel (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
The Purpose of Jesus’ Mission. The commission is due to the Father who tried to reconcile the world with himself by sending his Son to the mankind which became alienated from him. Jesus’ calling is not an invitation to a hermetically isolated community for a few elected Jews, who will later enjoy the blessings of their master’s proximity and the advantages of the security of his presence. Jesus’ calling viewed the commission. The way Jesus carried out his ministry of preaching and healing with the authority he received from God he sends his disciples to drive out demons and to heal diseases giving them the same authority and power. Service primarily means preaching the gospel. One of the aims of the appointment is preaching the gospel, which task the disciples fulfil obediently. Only Mark mentions the subject of preaching: the repentance. In the gospel of Mark the disciples do not proclaim the kingdom of God because they do not understand it yet, this is why they preach only about repentance so far. However, in the gospel of Matthew they preach about the coming kingdom of heaven. The apostles do not teach at Matthew, instead they are going to teach and ex-plain the commandments only. Matthew makes a certain distinction between the verbs ‘to preach’ and ‘to teach’. Jesus never does preach to the disciples but he does always teach them. Ulrich Luz points to the fact that in the usage of Matthew the two verbs sometimes appear side by side. That is why their distinction remains an open question. In the gospel of Luke the issue is also discussed that the disciples preach the kingdom of God. Luke speaks in 4,43 and 8,1 about the content and implementation of Jesus’ mission, which almost word by word occurs again with regard to the disciples in 9,2 and 9,6. Besides preaching, ministry means healing as well. In the disciples commission these two instructions are combined most of the time. We can find many examples to this parallel in the ministry of Jesus too. Healing was a sign that indicated the arrival of the kingdom of God. In the most significant manuscripts the command for healing does not occur in Mk 3,15 but Mk 6,13 speaks very clearly about the fact that the disciples healed people. The apostles healed many people by anointing them with oil. Using oil as ointment was a wide-spread practice in that time, however what the disciples did was more than the activity of their contemporaries, because they healed in the name of Jesus. The disciples were not theios andres despite the fact that they preached and healed, because they did all this by the power of Jesus, as his commissioned followers. They had to use this authority in order to heal the sick. This instruction is in imperative mood and is subordinated to the preaching. In Lk 9,1 the disciples did not get authority only, as in Mk 6,7 but also power to cure diseases and cast out demons. Many people healed the sick in the ancient times but the practice of Jesus and his disciples was different from theirs because besides healing they proclaimed the kingdom of God.